The bones of the world. - Berrios, Maria; Cervetto, Renata; Lagnado, Lisette; Pérez Rubio, Agustin; Biennale Berlin 2019 (Berlin : Berlin Biennale for Contemporary Art, 2020)
With works and contributions by: Marwa Arsanios, Amanda Mel Baggs, Felix Brüggemann, Flávio de Carvalho, Colectivo de Serigrafía Instantánea, Léo Corrêa, Die Remise (Ali Akyol, Jacqueline Aslan, Stefan Bast, Muriel Biedrzycki, Julia Brunner, Fatma Cakmak, Stefan Endewardt, Tobi Euler, Melina Gerstemann, Ayşe Güleç, Juanita Kellner, Angelika Levi, Carmen Mörsch, Shanti Suki Osman, Ayse Preissing, Markus Schega, Miriam Schickler, Aylin Turgay, and pupils from the Nürtingen and Heinrich-Zille elementary schools, with Çiçek Bacık, Aïcha Diallo, Saraya Gomis, Kotti-Shop, Annika Niemann, Tuğba Tanyılmaz), Feminist Health Care Research Group (Inga Zimprich/Julia Bonn), Andrés Fernández, Florian Gass, Till Gathmann, Mauricio Gatti, Eiko Grimberg, Sheroanawe Hakihiiwe, Âlut Kangermio, Mapa Teatro, Virginia de Medeiros, Marcelo Moreschi, Museo de la Solidaridad Salvador Allende, Mirja Reuter, Teatro da Vertigem, Teo, Cecilia Vicuña, Osías Yanov, and more.
This book is published on the occasion of the 11th Berlin Biennale for Contemorary Art curated by Maria Berrios, Renata Cervetto, Lisette Lagnado and Agustin Pérez Rubio.
boek